Optimal Control of Semiactive Two-Stage Vibration Isolation Systems for Marine Engines - YuanYuan Fang (Shock and Vibration)
To improve the vibration reduction performance of two-stage vibration isolation systems for marine engines under wide frequency band and multifrequency excitation, the magnetorheological (MR) damper is introduced into the vibration isolation system and an optimal controller is designed. Taking the test results of MR damper dynamic characteristics as sample data, the forward and inverse models of the MR damper are identified by the least square method and neural network (NN) method respectively, and the identification results are applied to semiactive control of the two-stage isolation system. Based on the analysis of vibration source, a six-degree-of-freedom mechanical model of two-stage system based on the MR damper is established. The optimal controller taking the minimum force transmitted from the engine to base as the control objective is designed. The system model and numerical simulation analysis are established using MATLAB. The results show that the isolation effect of optimal control is better than that of passive vibration isolation in the whole frequency band. In addition, good control effect is achieved in the low-frequency resonance region which is most concerned in engineering, which is of great significance to further improve the vibration reduction performance of marine engines.